The Causal Relationship between Trade Openness and Government Size in South Africa: Array - Maluleke, Glenda (Acta Universitatis Danubius. Œconomica, 2020)
This study empirically examines the causality between government size and trade openness including economic growth as an intermittent variable from 1980 to 2018 in South Africa. The study employed the Johansen-Juselius cointegration and Granger causality test. The results revealed that there is a long-run relationship between government size and trade openness. The Granger causality test revealed that there is a unidirectional causality from trade openness to government size. Therefore, the study does find support for a compensation hypothesis in South Africa.